2016
DOI: 10.1590/0103-5150.029.002.ao12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional capabilities in children with Down Syndrome

Abstract: Introduction: Down Syndrome (DS) is a chromosomal abnormality characterized by mental retardation of varying degrees and is one of the most commonly found chromosomal aberrations, presenting motor delay such as muscular hypotonic, balance disorders, motor coordination and gait changes. Objective: To evaluate the functional capabilities in children with Down syndrome through the Pediatric Evaluation of Disability Inventory (PEDI). Methods: 20 children of both sexes, 10 with normal motor development (Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In infants with DS, the basic motor milestones occur later in comparison to children who do not have the syndrome, and for this reason, it is necessary to have an early intervention in these children to favor the stimulation of motor development [1]. In the present study, an early intervention was provided with the application of the Bobath Concept, and improvement in motor skills was seen, mainly in the prone position, which influences crawling activity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In infants with DS, the basic motor milestones occur later in comparison to children who do not have the syndrome, and for this reason, it is necessary to have an early intervention in these children to favor the stimulation of motor development [1]. In the present study, an early intervention was provided with the application of the Bobath Concept, and improvement in motor skills was seen, mainly in the prone position, which influences crawling activity.…”
Section: Discussionmentioning
confidence: 74%
“…Page 02 of 09 Down syndrome (DS) is a genetic disorder that occurs due to the presence of an extra chromosome, namely a trisomy of chromosome 21 [1]. This syndrome is commonly characterized by being related to muscle hypotonia, ligament laxity and muscle weakness, which results in changes in dynamic balance and postural control [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be inferred that there are delays in all aspects of the development of the body schema of DS children that are due to perceptual and motor deficits, which are responsible for the formation of the same and functional activities, and there must be an adequate stimulation that properly addresses the lags presented in each individual [ 58 ]. Differences in the development of gross and fine motor skills appear in DS children in the first months of life, with more active children achieving more marked development, highlighting the adaptability of early childhood and the importance of early stimulation [ 68 ], which also contributes to the development of functional skills, where people with DS underperform others [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The knee angular amplitude, which displays much higher variation in all children throughout the final stages of the intervention, was another important metric sensed. It is important emphasize that other studies demonstrated various exercises using commercial video games with important outcomes for task efficacy and attentional selection, but without movement identification and proprioceptive analysis [10], [28], [37].…”
Section: Discussion and Remarksmentioning
confidence: 99%